Do Conventional and Islamic Rural Banks Differ in Financial Performance: Empirical Evidence from Bogor - Fiona Andriyan Zaharani; Muhammad Nur Faaiz F Achsani; Asep Nurhalim (School of Business, IPB University (SB-IPB), 2026)
Background: Rural banks play an important role in supporting micro and small businesses in Indonesia. Despite operating under different banking principles, both conventional rural banks and Islamic rural banks face similar challenges in maintaining their financial performance. In Bogor, where both types of institutions are highly concentrated, comparing their financial performance becomes important to assess whether differences in banking type led to different financial outcomes.Purpose: This study aims to examine whether banking type affects the financial performance of conventional rural banks and Islamic rural banks in Bogor, as measured by return on assets (ROA) and non-performing loans/financing (NPL/NPF).Design/methodology/approach: This study employs a quantitative explanatory approach using panel data from five rural banks and five Islamic rural banks in Bogor over the period 2020–2024. The analysis uses panel data regression, with the random effect model selected as the most appropriate specification, to estimate the effect of banking type and internal as well as macroeconomic variables on financial performance.Findings/Results: The results show that banking type does not have a statistically significant effect on either ROA or NPL/NPF. ROA is mainly influenced by internal factors, where the capital adequacy ratio has a positive and significant effect, while bank size and financing ratio have significant negative effects. Meanwhile, no independent variable is found to significantly affect NPL/NPF. Conclusion: That profitability is more closely associated with internal financial conditions, while financing risk is more likely shaped by management quality and other factors beyond the model.Originality/value (State of the art): This study contributes to the literature by providing direct local-level evidence on the comparative financial performance of rural banks and Islamic rural banks in Bogor using both profitability and risk indicators in a one-panel regression framework. It highlights that the distinction between conventional and Islamic banking types is less decisive than internal bank conditions in explaining performance differences. Keywords:conventional rural banks, financial performance, Islamic rural bank, banking type, panel data